EFFECT OF SPICES MIXTURE ON BLOOD GLUCOSE AND LIPIDS PROFILE IN EXPERIMENTALLY - INDUCED OXIDATIVE STRESS FEMALE RABBITS - Al-Jowari, Suha (Iraqi Journal of Science, 2024)
The effect of spices mixture on blood glucose and lipids profile in oxidativestress rabbits was studied. Twenty female rabbits were randomly divided into fourgroups (five animals in each group). The first group was subjected to oxidativestress by the ad libitum supply of drinking water containing 0.5% H2O2. The secondgroup was supplied with pellets containing 20% spices mixture. The spices mixtureis composed of cinnamon, turmeric and cumin powder. The third group wassubjected to H2O2 (0.5%) and supplied with pellets containing 20% spices mixture.The last group was considered as control and supplied with pellets and water. Theperiod of experiment was lasted for 21 days.The results showed that there was a significant (P<0.05) decrease in glucose,cholesterol, triglyceride, LDL-C and VLDL-C concentration, except HDL-Cconcentration which increased significantly (P<0.05) in the groups exposed withspices mixture and spices mixture + hydrogen peroxide compared with stressanimals.In conclusion, this study revealed that the supplementation of diets with moderateamounts of spices mixture might have some beneficial effects in oxidative stressconditions and reducing the risk of diabetes and atherosclerosis diseases throughimproving glucose and lipid metabolism.Therefore, the active materials in these natural plants might extract and use indiabetes and atherosclerosis drug industry from natural resources.